Mary Vance Trent papers - Trent, Mary Vance, 1914-1998.
Correspondence, memoranda, family papers, reports, speeches, writings, photographs, clippings, travel notes, and printed matter relating primarily to Trent's career as a foreign service officer for the U.S. State Department, in particular her assignments in Indonesia (1957-1958 and 1964-1967), Wellington, N.Z. (1969-1972), and Saipan, Trust Territory of the Pacific Islands (Micronesia) (1972-1974), and as a lecturer for the Smithsonian Institution's travel program. Of particular interest are letters from Trent to her sister, Madeline Trent, religious writings and short stories by Trent's father, Ray S. Trent, and a letter by Trent's Confederate ancestor, C. W. Deane, from the Civil War battlefield at Wilson Creek, Missouri.
Subjects include Trent's activities as U.S. liaison for East Asian affairs to the United Nations and as advisor and director of the U.S. Office for Micronesian Status Negotiations, self-government in Micronesia, the 1965 anti-Communist uprising in Indonesia which replaced President Soekarno with General Soeharto, Marshall Green, the former ambassador to Indonesia, the status of women in Indonesia and other countries, a training course for diplomats' wives taught by Trent from 1962 to 1964, the women's pages of the Christian Science Monitor covering topics such as women's liberation and equal rights, Trent's childhood, family, and religious faith (Christian Science), and the Girl Scouts, including Trent's 1932 trip to the inauguration of Our Chalet, the Girl Guide and Girl Scout headquarters, in Adelboden, Switzerland.
Foreign service officer and lecturer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Division and at
Keywords: Deane, C. W. -- Correspondence; Green, Marshall; Soeharto, -- 1921-2008.; Soekarno, -- 1901-1970.; Trent, Madeline -- Correspondence; Trent, Ray S; Trent family; United States. -- Department of State. -- Officials and employees; United States. -- Office for Micronesian Status Negotiations -- Officials and employees; Our Chalet (Adelboden, Bern, Switzerland); Smithsonian Institution; United Nations; Christian Science monitor; Anti-communist movements -- Indonesia; Christian Science; Democracy -- Micronesia (Federated States); Diplomatic and consular service, American; Diplomats' spouses -- Education -- United States; Equality before the law -- United States; Feminism -- United States; Girl Scouts; Representative government and representation -- Micronesia (Federated States); Women -- Legal status, laws, etc; Women -- Legal status, laws, etc. -- Indonesia; Indonesia -- Foreign relations -- United States; Indonesia -- Politics and government -- 1950-1966.; Indonesia -- Politics and government -- 1966-1998.; Micronesia (Federated States) -- Foreign relations -- United States; Micronesia (Federated States) -- Politics and government; Missouri -- History -- Civil War, 1861-1865.; New Zealand -- Foreign relations -- United States; United States -- Foreign relations -- Indonesia; United States -- Foreign relations -- Micronesia (Federated States); United States -- Foreign relations -- New Zealand; Foreign service officers